Gender-based violence in Lima and Callao’s urban areas and urban fringe 2007 - 2010 - Mascaro-Sánchez, Pedro (2012)
Objectives: To determine and compare gender-based violence characteristics in urban populations and urban fringe. Design: Comparative cross-sectional prospective study. Setting: School of Obstetrics, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Women from Lima and Callao. Interventions: Between 2007 and 2010 a structured interview was applied to 3 971 women from urban areas and marginal urban areas of Lima and Callao. Women included were local residents, and women with obvious psychological problems and speech problems were excluded. Data was analyzed with descriptive statistics and chi-square method, with significant level p <0,05. Main outcome measures: Violence. Results: Thirty-nine per cent of respondents were between 20 to 24 years of age; 47% identified physical violence, similar at urban and marginal urban areas. Pushing and slapping were the most frequent violence forms at both areas. Psychological violence consisted in shouting, possessiveness and jealousy at both urban and marginal urban areas. Spending without consulting the couple was slightly higher at marginal urban areas (49%) than in urban areas (42%). Attempt to have sex against will was the most frequent type of violence (37%), more in the urban area (41%) than in marginal urban areas (34%). Conclusions: Episodes of physical, psychological, economic, and sexual violence episodes were similar for urban and urban fringe areas, but marginal sexual violence was more frequent in the urban area.